Parameter Biologi dan Demografi Parasitoid Diadegma semiclausum Hellen (Hymenoptera : Ichneumonidae) pada Plutella xylostella L. (Lepidoptera : Plutellidae) - NI PUTU NIA KUMARAWATI; I WAYAN SUPARTHA; KETUT AYU YULIADHI (Fakultas Pertanian Universitas Udayana, 2018)
Biological and Demographic Parameters of Parasitoid Diadegma semiclausum Hellen (Hymenoptera: Ichneumonidae) on Plutella xylostella L. (Lepidoptera: Plutellidae). Diadegma semiclausum Hellen (Hymenoptera: Ichneumonidae) is one of the parasitoid larvae which attacks Plutella xylostella (Lepidoptera: Plutellidae) effectively. This research was aimed to know the biology of parasitoid D. semiclausum in broccoli. The research was carried out in a laboratory by observing the development of parasitoid, fecundity, longevity the males and females as well as parameters demographic of D. semiclausum. The results showed that immature development time of D. semiclausum parasitoid from egg up to adult the imago was 10.65 ± 0.63 days, with the number of fecundity was 22.9 grains. Longevity of male imago of D. semiclausum was 12.10 ± 0.74 days and imago of females 9.80 ± 1.87 days. Parameters demographic of D. semiclausum showed that net reproduction rate (R0) was 22.11 per generation, intrinsic growth rate (r) was 0.18 per day, limited increased rate (?) was 1.16 individuals per day, generation time (T) was 17.50 day.